Evaluation of Continuous Assessment Practice by University Lecturers - Patrick U. Osadebe (Institute of Advanced Engineering and Science, 2015)
The study evaluated the extent to which Continuous Assessment (CA) was practiced by university lecturers in Delta State University, Abraka, Nigeria. The evaluation of continuous assessment focused on the cognitive, affective and psychomotor domains of students’ behaviour. That is teaching and learning should focus on these areas. Two research questions were raised, and two hypotheses were tested to achieve the purpose of the study. A sample of 200 lecturers was randomly selected using simple random sampling and stratifies random sampling techniques. A 5-point scaled questionnaire was used as an instrument to collect data. The validity of the instrument was determined through expert judgement and factor analysis. Thus the instrument has face and construct validities. The reliability of the instrument was established through Cronbach Alpha. A reliability coefficient of 0.86 was obtained as a measure of internal consistency. The data collected were analyzed. The research questions were answered with the use of mean. The hypotheses were tested with Z-test at .05 level of significance. The result of evaluation revealed that the extent to which university lecturers practice continuous assessment with emphasis on the cognitive, affective and psychomotor domains of students’ behaviour was low. There was no significant difference between male and female as well as junior and senior lecturers on the practice of continuous assessment in the university. It was noted that there should be a continuous and effective monitoring of continuous assessment practice by the university lecturers.